Penerapan Algoritma A-star dan Brute Force pada Aplikasi Jakvel (Jakarta Travel) Berbasis Android - Andryana, Septi; Andrianingsih, Andrianingsih; Farhan, Naif (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2021)
The city of Jakarta has several main tourist attractions that are interesting to visit. As the Capital of the State of Indonesia, it will certainly be ogled and visited by local and foreign tourists. However, there is limited information, tourists from outside the Jakarta area lack complete information on tourism in the city of Jakarta and the roads that must be taken to tourist sites, due to the number of roads and heavy traffic, this makes it a problem when you want to vacation in the city of Jakarta. Therefore, the author designed an application called Jakvel based on Android, this application provides information and looks for the shortest path to tourist sites for tourists who want to vacation in Jakarta. In this study using the A-star and Brute Force algorithms. The A-star algorithm will be applied to find the shortest path to tourist sites and the brute force algorithm is used to search for words (strings) in selecting tours. With this application, it is hoped that it will make it easier for tourists outside the Jakarta area to find out tourist information and help find the shortest path to locations in the city of Jakarta. After testing of 10 tourist sites to determine the shortest path by comparing the A-star algorithm with Google Maps based on Android, with a 70% success rate in finding the shortest path using the A-star algorithm and the results of string search testing using the Brute Force algorithm have a percentage of 100% accurate